2015
DOI: 10.4236/jbm.2015.33012
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Health-Promoting Lifestyle of Student Nurses in Malaysia

Abstract: Studies have indicated that lack of regular physical exercise and not adhering to a health-promoting lifestyle among student nurses are barriers to their encouraging patients to exercise. On the other hand, nurses who personally embrace physical activity are more likely to encourage their patients to improve their health through physical activity or diet. As a result, promoting an active and healthy lifestyle among student nurses is important because this has a crucial role in their subsequently encouraging he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
(33 reference statements)
4
22
1
Order By: Relevance
“…The baseline evaluation of the adolescents' lifestyle showed that the domains with the lowest scores were the spiritual health and the health responsibility and the highest scores domains were the interpersonal relations and positive life perspective, similar to other studies (Kim & Kim, ; Sousa, Gaspar, et al, ). It should be noted, however, that other researchers found higher lifestyle scores in the spiritual domain and health responsibility (Golmakani, Naghibi, Moharari, & Esmaily, ; Shariferad, Shojaeezadeh, Tol, & Tavassoli, ) and lower scores in physical activity (Geok et al, ; Golmakani et al, ; Shariferad et al, ). Our data suggest that, although adolescents have good interpersonal relationships and a positive life perspective, they do not feel responsible for promoting their health.…”
Section: Discussionmentioning
confidence: 88%
“…The baseline evaluation of the adolescents' lifestyle showed that the domains with the lowest scores were the spiritual health and the health responsibility and the highest scores domains were the interpersonal relations and positive life perspective, similar to other studies (Kim & Kim, ; Sousa, Gaspar, et al, ). It should be noted, however, that other researchers found higher lifestyle scores in the spiritual domain and health responsibility (Golmakani, Naghibi, Moharari, & Esmaily, ; Shariferad, Shojaeezadeh, Tol, & Tavassoli, ) and lower scores in physical activity (Geok et al, ; Golmakani et al, ; Shariferad et al, ). Our data suggest that, although adolescents have good interpersonal relationships and a positive life perspective, they do not feel responsible for promoting their health.…”
Section: Discussionmentioning
confidence: 88%
“…5,6,10 The underweight in the study subjects was due to the habit of skipping meals has been investigated in the present study. The percentage of student who skipped the meal is quite high among the underweight group i.e.…”
Section: 3mentioning
confidence: 99%
“…1 Nursing students, who are responsible for client health promotion education, are important to the success of this paradigm shift from a disease model to health promotion. 5 Health-promoting behaviour is an important concept in nursing, because most of nursing activities involve healthcare education. Nurses are often expected as role models of health promoting lifestyles and as leaders to activate communities for health promotion.…”
mentioning
confidence: 99%
“…Overweight or obesity is the result of an imbalance between the calories consumed and those burnt by a given person. Malaysia ranks sixth in terms of obesity in the Asia-Pacific region and first for obesity and diabetes in South-East Asia (Geok et al, 2015). Statistics released by the National Health and Morbidity Surveys confirm that 17.7% of Malaysians 18 years old and above struggle with obesity and about 1 out of 3 Malaysia are overweight (Ministry of Health Malaysia, 2016).…”
Section: Introductionmentioning
confidence: 99%